Parametric simulations of composite barrier FTJs under external bias at room temperature - Catalin Tibeica; Titus Sandu; Oana Nedelcu; Rodica Plugaru; Neculai Plugaru (Results in Physics, 2023)
A study on a parametrized model of a composite barrier ferroelectric tunneling junction (FTJ), three-interface system with a non-polar dielectric layer, under an external bias voltage, Va, and at room temperature, using Finite Element Method-based simulations, has been performed. The approach involves the Thomas–Fermi model assuming incomplete screening of polarization charges for building the energy barrier profile, and numerically simulates the electron transport through the barrier by bias-voltage-dependent tunneling, using Tsu-Esaki formulation. That naturally includes the temperature dependent contributions to the total current density. The tunneling electroresistance ratio (TER) and current densities are computed considering variations of a large set of parameters that describe the composite barrier system in realistic physical range of values with respect to a reference (prototypical) system. In this study, the parametric simulations were performed starting from selected data reported on the SrRuO3/SrTiO3/BaTiO3/SrRuO3 heterostructure. The most important results of our work can be stated as follows: (i) The simulations prove to be a reliable approach when we are interested in the prediction of FTJ characteristics at temperatures close to 300 K, and (ii) We show that several configurations with large TER values can be predicted, but at the expense of low current densities in the ON state. We suggest that the results may be useful for assessing the FTJ performances at ambient temperature, as well as to design preoptimized FTJs by using different combinations of materials to comply with a set of properties of a specific model.